(3GdaQGTGJ GdMRjfIs ((3GdbGgQIs (3hKjbIs, 2006)
(3GdaQGTGJ OGFeG eSQhQI aQMI PGJ MQjI hWGbI JWjQ gfG hgfGc(B..(3JfJbd Hjf GdRghQ GdLejdI hGdMbhd GdhGSYI (B..(3EPf eG GdPj LYdgG MRjfI? Efg SGej GdhdO GdTbj eG OhQ CNJg CSeGA?cja JYGedJ eYg?eGPG bGdJ dg?eG TYhQ SGej?s
(3GdbUI(B--s (3GdfTjO(B--s (3dYHI GdMQha GdCHLOjI(B--s (3dYHI GdCTjGA(B--s (3dYHI GdJdhjfs
(3ef (B4 (3Edj (B9 (3SfhGJs
2
Keywords: (3GdaQGTGJs -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs